2021
DOI: 10.1021/acsami.1c11212
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Thermal Negative Effect and Maintaining High-Temperature Steady Electrical Performance of Triboelectric Nanogenerators by Employing Phase Change Material

Abstract: Triboelectric nanogenerators (TENGs) are newly developed energy-harvesting mechanisms, which can efficiently transmute irregular mechanical energy into scarce electrical energy. However, the electrical performance of TENGs shows a decreasing tendency with the increase in temperature, and the negative effect caused by friction heat and operating environmental thermal stresses for the output performance, durability, and reliability are still a bottleneck, restricting the practical application of TENG electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…However, the thermal enthalpy still remains at an ideal level. Figure c shows that the melting enthalpy of EPU@PW is significantly higher than the recently reported results by electrospinning (in a reasonable temperature range for human life between 22 and 46 °C), , which reveals that EPU@PW is a promising candidate for a responsive thermoregulatory textile. As seen in Figure h, the DSC thermograms exhibit a favorable coincidence regarding the locations and intensities of the melting and cooling peaks in 50 cycles, demonstrating the stable reversibility of the phase change behavior.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the thermal enthalpy still remains at an ideal level. Figure c shows that the melting enthalpy of EPU@PW is significantly higher than the recently reported results by electrospinning (in a reasonable temperature range for human life between 22 and 46 °C), , which reveals that EPU@PW is a promising candidate for a responsive thermoregulatory textile. As seen in Figure h, the DSC thermograms exhibit a favorable coincidence regarding the locations and intensities of the melting and cooling peaks in 50 cycles, demonstrating the stable reversibility of the phase change behavior.…”
Section: Resultsmentioning
confidence: 61%
“…Coaxial electrospinning has been explored to produce core–sheath structured phase change fibers. In this process the PCMs are encapsulated in the center of the fiber to solve the leakage issue. Additionally, the high aspect ratio of the ultrafine fibers endows the prepared composite membranes with favorable flexibility. Most importantly, the large specific surfaces of the fibrous membrane provide a platform for functionalized surface modifications.…”
Section: Introductionmentioning
confidence: 99%
“…74,75 However, the challenges in exploring triboelectric materials with low cost and high performance still exist and have aroused the interests of many researchers. 76,77 Furthermore, various approaches, such as energy extraction enhancement circuit, 78 have been reported to significantly enhance the energy conversion efficiency. [79][80][81][82] In 2019, Lee et al reported an overview of harvesting mechanical energy via TENG technology, which focused on the surface modification methods beyond the limitations of structural parameters and materials.…”
Section: Harvesting Human Mechanical Energy With Tengs For Power Supplymentioning
confidence: 99%
“…[100,101] Currently, the commercial thermoelectric module is the main component for thermoelectric conversion in energy generation systems associated with PCMs, and a stiff thermoelectric module without flexibility is used, even in heat-to-electrical energy conversion systems with thermally conductive materials. [102,103] In addition to thermoelectric modules, the integration of PCMs with solar cells (Figure 6b), [104] triboelectric nanogenerators (Figure 6c), [105] and pyroelectric energy harvesting systems (Figure 6d), [106] has been developed. Unlocking opportunities for more promising energy conversion systems, such as flexible thermoelectric modules for wearable products, ion-type thermoelectric generators for integrated heat collection devices, and solar steam generation for all-weather modes, remains an elusive goal.…”
Section: Emerging Energy Conversionmentioning
confidence: 99%
“…[120] Recently, a freeze-spinning method integrating solution spinning with freeze-casting has been proposed to fabricate a thermoregulating phase change textile capable of passive heating and cooling with zero energy Figure 6. Integration of PCMs with other energy conversion and generation devices: (a) thermoelectric modules, [99] (b) solar cells, [104] (c) nanogenerators, [105] and (d) pyroelectric systems. [106] a) Reproduced with permission.…”
Section: Thermal Management and Regulationmentioning
confidence: 99%